Intraindividual right-left comparison of sonographic features in polycystic ovary syndrome (PCOS) diagnosis - Köninger, Angela; Koch, Laura; Edimiris, Philippos; Nießen, Stefanie; Kasimir-Bauer, Sabine; Kimmig, Rainer; Strowitzki, Thomas; Schmidt, Börge (European journal of obstetrics & gynecology and reproductive biology, 2014)
Objective - Sonographic features of polycystic ovaries consist of elevated antral follicle count or ovarian volume of at least one ovary. The aim of this prospective cross-sectional study was to estimate intraindividual differences in sonographic measurements between the both ovaries of PCOS patients and controls and clinical consequences. - Study design - Both ovaries of 85 PCOS patients and 48 controls were scanned transvaginally and agreement of sonographic measurements was analyzed using the Bland-Altman method. Concordance correlation coefficients (CCC) were computed. - Results - Mean differences between right and left ovaries were 0.24 (95% confidence interval [95% CI]: −0.32-0.80) follicles for AFC and 1.14 (95% CI: 0.34-1.92)ml for OV in the whole study population, 0.14 (95% CI: −0.68-0.96) follicles for AFC and 1.48 (95% CI: 0.39-2.58)ml for OV in PCOS patients, 0.42 (95% CI: −0.19-1.02) follicles for AFC and 0.53 (95% CI: −0.50-1.56)ml for OV in controls. Rather wide limits of agreement and low CCCs (<0.7 for all estimates) indicated poor agreement between the ovaries for both sonographic measurements. Width between lower and upper limits of agreement was higher for PCOS patients than for controls. 23.5% of the PCOS patients showed polycystic ovarian morphology (PCOM) only in one ovary, resulting in 9.4% potentially missed PCOS diagnosis according to the Rotterdam ESHRE/ASRM-Sponsored PCOS Consensus Workshop Group. - Conclusion - Substantial differences in antral follicle count and ovarian volume between the right and left ovary were observed. In approximately 10% of the PCOS patients in our study only the examination of both ovaries has led to a reliable diagnosis of PCOS. In clinical practice it is recommended to scan both ovaries for a reliable diagnosis of abnormal sonographic findings in PCOM and PCOS diagnosis.
Gesehen am 15.07.2020